ответ: x₁=(-1+√17)/2 x₂=(-1-√17)/2.
объяснение:
15/(x²+x+1)=(x+1)²+x²
15/(x²+x+1)=x²+2x+x²
15/(x²+x+1)=x²+x+x+x²
15/(x²+x+1)=x²+x+1+x²+x+1-2
15/(x²+x+1)=2*(x²+x+1)-2
пусть x²+x+1=t ⇒
15/t=2*t-2
15=2t²-2t
2t²-2t-15=0 d=64 √d=8
t₁=x²+x+1=-3 x²+x+4=0 d=-15 x∈∅
t₂=x²+x+1=5 x²+x-4=0 d=17 √d=√17 x₁,₂=(-1±√17)/2.
1) x³ + 4x² - x = 4
x³ + 4x² - x - 4 = 0
(x³ + 4x²) - (x + 4) = 0
x²(x + 4) - (x + 4) = 0
(x + 4)(x² - 1) = 0
(x + 4)(x - 1)(x + 1) = 0
или x + 4 = 0 и тогда x₁ = - 4
или x - 1 = 0 и тогда x₂ = 1
или x + 1 = 0 и тогда x₃ = - 1
ответ : - 4 ; - 1 ; 1
2) 2x³ + x² - 8x = 4
2x³ + x² - 8x - 4 = 0
(2x³ - 8x) + (x² - 4) = 0
2x(x² - 4) + (x² - 4) = 0
(x² - 4)(2x + 1) = 0
(x + 2)(x - 2)(2x + 1) = 0
или x + 2 = 0 и тогда x₁ = - 2
или x - 2 = 0 и тогда x₂ = 2
или 2x + 1 = 0 и тогда x₃ = - 0,5
ответ : - 2 ; - 0,5 ; 2
Поделитесь своими знаниями, ответьте на вопрос:
40 решите неравенство lg2 (x+2)2(x+5)/5 < lg2 (x+5)/20
!